Analysis of epidemiological characteristics of age-associated diseases (hypertensive diseases and type 2 diabetes) in 2011–2021: federal, district and regional level - U. R. Saginbaev; V. V. Lyutsko; T. A. Akhmedov; S. A. Rukavishnikova (Сибирский научный медицинский журнал, 2024)
Age-associated diseases (AAD) remain an urgent issue for individuals of different age groups. In the context of the recently completed COVID-19 pandemic, there is an acceleration of aging processes. From a clinical point of view, the early manifestation of AAD corresponds to accelerated aging. The study of AAD epidemiological characteristics in the aspect of different age groups seems very relevant. Aim of the study was to investigate the epidemiological characteristics of AAD (on the example of hypertensive diseases and type 2 diabetes mellitus) at the federal, district and regional levels. Material and methods. The materials were the statistical collections of the Ministry of Health of Russia for 2011–2021. An assessment of the incidence rate, trend, rate of increase/decrease in incidence, the ratio of the incidence rate among people over working age to the incidence rate of the adult population (age-specific incidence index, ASII) was carried out. Units of observation: hypertensive diseases; type II diabetes mellitus. Results and discussion. In 2011–2021, an unfavorable upward trend in morbidity was observed at the federal (Russian Federation), district (the North-West Federal District) and regional (Saint-Petersburg) level. However, in terms of the rate of increase in morbidity and ASII, specific features were found for the considered nosologies: hypertensive diseases were characterized by an increase in ASII, and for type 2 diabetes, on the contrary, a decrease in VID (“rejuvenation” of AAD).